DIGITALISASI PENDIDIKAN HUKUM - Susanto, Anthon F.; Septianita, Hesti; Tedjabuana, Rosa; Pratama, Mohammad Alvi (Faculty of Law, Universitas Pasundan, 2022)
The world has changed into a reality engineered through logic digital known as artificial intelligence. When the intelligence develops in rapid fashion into conscience like human, the potential game, website and other network and digital facility will drastically be increasing. Methods used is a participative-mixed method model of research with four approaches which are philosophical, conceptual, socio-legal and textual-critique approaches with literature study data collecting technique. In this era of artificial intelligence, legal education should be reborn with new face, education with commitment to respond digital development without ignoring the value of wisdom. Legal education will lead to the development of practical skill and is based on values of wisdom. Legal education should establish cultural-based curriculum as legal education is an education of behavior. Legal education should be adapted with global values but paying attention to local aspects or on the other hand maintaining rational education and constructing sense of logic and retaining good practical skill and the concern to marginalized community. That is what future legal education should be. Keywords: Digitalization, Artificial Intelligence, Legal Education.